Photochemistry of 3-amino-1, 2-benzisoxazole: unexpected photoisomerization of an amino-spiro-2H-azirine to a 1H-diazirine. Issue 46 (16th November 2016) - Nunes, Cláudio M.; Pinto, Sandra M.V.; Reva, Igor; Fausto, Rui
Graphical abstract: Highlights: Photochemistry of 3-amino-1, 2-benzisoxazole was studied in low-temperature matrix. Reactive intermediates were characterized experimentally by IR spectroscopy. The transformation of an amino-spiro-2 H -azirine into a 1 H -diazirine was discovered. Abstract: UV irradiation of 3-amino-1, 2-benzisoxazole isolated in an argon matrix leads to the formation of an amino-spiro-2 H -azirine. The amino-spiro-2 H -azirine was found to photoisomerize back to 3-amino-1, 2-benzisoxazole and also to a 1 H -diazirine, which isomerizes to a carbodiimide. All the reported species were characterized experimentally by IR spectroscopy and confirmed by comparison with theoretical IR spectra. The discovery of the transformation of an amino-spiro-2 H -azirine into a 1 H -diazirine is unprecedented in the chemistry of reactive intermediates.